No Harm Principle: Reconstructing John Stuart Mill’s Thought in On Liberty to Foster Epistemic Responsibility in Addressing the Ethical Consequences of Post-Truth - Yohanis Elia Sugianto (Seminari Tinggi St. Fransiskus Xaverius Ambon, 2025)
The post-truth era, marked by disinformation, hate speech, and algorithmic polarization, poses significant ethical and epistemic challenges to democratic societies. This article examines the relevance of John Stuart Mill’s Harm Principle in On Liberty (1859) as a normative framework for addressing these challenges. Through a philosophical analysis, the study reconstructs the Harm Principle to encompass epistemic, psychological, and democratic harms caused by unchecked freedom of expression in digital spaces. By analyzing phenomena such as filter bubbles, echo chambers, and disinformation campaigns, the article proposes practical solutions—digital literacy, ethical communication, and algorithmic transparency—to foster epistemic responsibility. Case studies, including the 2016 U.S. election misinformation and COVID-19 vaccine disinformation, illustrate the real-world implications of these harms. Empirical data on digital literacy and algorithmic bias further support the proposed framework. The findings highlight the enduring relevance of Mill’s thought while acknowledging limitations, such as implementation challenges and the need for complementary perspectives. This study contributes to political philosophy and communication ethics by offering a reconstructed Millian framework to navigate the complexities of digital public spheres, with implications for policy, education, and democratic deliberation.